Considerações sobre a aplicação de unidades potencialmente significativa para lógica de programação - Soltoski, Roberto César (2022)
Algorithms and Programming Logic I (LP I) are essential for students in Computer Science courses. Nevertheless, through the experience and literature review carried out, it appears that a significant portion of these students have difficulties in understanding and applying such contents, leading to high rates of failure and dropout, being one of the causes for discontinuing the course. In order to contribute to a better understanding of this problem and to discuss pedagogical actions which aimed to improve students learning, eight Potentially Meaningful Teaching Units (PMTUS) were developed in this research, which are didactic sequences based on the Theory of Meaningful Learning (TML). Its instructional objectives, ranging from initial concepts to Selection and Repetition Structures, were defined following the recommendations of the Brazilian Computer Society (BCS) and its planning considered the dimensions of knowledge and cognitive processes of Bloom’s Taxonomy. In a case study, the PMTUS were used with the class of students from the school year of 2020 linked to the LP I discipline, from the Technical Course in Informatics Integrated to High School at the Goioerê Advanced Campus - Federal Institute of Paraná (IFPR). The collected data were organized into digital files and analyzed qualitatively and quantitatively, emphasizing three tests that were applied and verified for their Validity and Reliability. In these tests, Content Validity was considered predominantly Good and Appearance Validity, predominantly Great. Reliability by Internal Consistency obtained Cronbach’s Alpha of 0.781, meaning high or substantial. The joint analysis of Validity and Reliability of the four questions contained in the three tests indicated that the first question presented strong Validity and Reliability; the second was moderate; and the third and fourth questions were not acceptable. An Analysis of Variance (ANOVA) indicated that there was a positive effect on the averages of the students who participated in the case study in 2020 in comparing them with the averages of the students of the 2019 and 2018 classes, with P-value 0.0016, for a level of significance of 5%. It was possible to identify evidence of Significant Learning by the students of the class of 2020. For this, Exploratory Analysis was used in the three applied tests, besides, responses, explanations and justifications given by the students when solving certain activities were also observed. Such evidences were perceptible in different situations, from the one in which prior knowledge was compared and the improvements achieved throughout the development of the discipline, as far as experiments with robotics in addition to the verifications as to whether certain contents were properly used in at least one of the tests (OR Test) and on all three tests (AND Test). One of the factors to which these evidences are attributed is the increasing in the differentiation of the contents covered in the PMTUS, which have been integrated into the students’ cognitive structure in an increasingly balanced way. Moreover, there was no obliteration, since as time had passed, such contents were used in other activities, which, in general, were resolved adequately